2017
DOI: 10.3354/meps12363
|View full text |Cite
|
Sign up to set email alerts
|

Glacial dropstones: islands enhancing seafloor species richness of benthic megafauna in West Antarctic Peninsula fjords

Abstract: The West Antarctic Peninsula (WAP) margin is dominated by glaciomarine fjords and has experienced rapid climate warming in recent de cades. Glacial calving along the peninsula delivers icerafted debris (e.g. dropstones) to heavily sedimented fjord basins and the open continental shelf. Dropstones provide hard substrate, increase habitat heterogeneity, and may function as island habitats surrounded by mud. We used seafloor photographic transects to evaluate the distribution and community structure of Antarctic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Our photographic survey also provides further evidence that ice-rafted dropstones are important as sites of benthic diversity. In a photographic survey off the western Antarctic Peninsula at water depths of 437 to 724 m, Ziegler et al (2017) found that although dropstones occupied < 1% of the total seafloor area surveyed, they contributed 20% of the megabenthic invertebrate species diversity. Ziegler et al (2017) also captured images of the channichthyid Chaenodraco wilsoni guarding nests of eggs laid on dropstones.…”
Section: Comparison With Previous Studies and Other Areasmentioning
confidence: 99%
“…Our photographic survey also provides further evidence that ice-rafted dropstones are important as sites of benthic diversity. In a photographic survey off the western Antarctic Peninsula at water depths of 437 to 724 m, Ziegler et al (2017) found that although dropstones occupied < 1% of the total seafloor area surveyed, they contributed 20% of the megabenthic invertebrate species diversity. Ziegler et al (2017) also captured images of the channichthyid Chaenodraco wilsoni guarding nests of eggs laid on dropstones.…”
Section: Comparison With Previous Studies and Other Areasmentioning
confidence: 99%
“…Lithogenic sediment production by cold-based glaciers is weak in this subpolar fjord, and therefore, (1) biogenic sediment production is relatively important, and (2) rates of burial disturbance are presently slow. This slow burial allows development of abundant, biodiverse benthic and demersal communities of megafauna in the middle and inner Andvord Bay (Grange et al, 2017;Grange & Smith, 2013;Ziegler et al, 2017), compared to Svalbard fjords (Górska & Włodarska-Kowalczuk, 2017;Renaud et al, 2007;Włodarska-Kowalczuk et al, 2012). Ultimately, glacial meltwater and sediment production are expected to increase in response to regional warming trends (e.g., Koppes et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal plankton blooms can be intense and cause decreased light transmission in surface waters, especially in the middle basins (Pan et al, 2019). Recent studies indicate large values for summer biomasses of krill and humpback whales (Espinasse et al, 2012;Nowacek et al, 2011) as well as high abundances and biodiversity of fjord megabenthos on soft sediments and dropstones (Grange et al, 2017;Grange & Smith, 2013;Ziegler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted as part of LARISSA have also highlighted the dramatic differences between the rich benthic assemblages in fjords along the western Antarctic Peninsula and those on the open western Antarctic Peninsula shelf and in the Weddell Sea (Grange and Smith, 2013). Dropstone habitats add significantly to the diversity of benthic megafauna (Ziegler et al, 2017), indicating that ice-shelf collapse and massive dropstone production substantially alters formerly sub-ice-shelf ecosystems. Furthermore, LARISSA studies revealed that, in recent decades, a large population of king crabs crossed onto the western Antarctic Peninsula continental shelf.…”
Section: Ongoing Ecosystem Changesmentioning
confidence: 99%